RAINFALL THRESHOLDS FOR FLOOD EARLY WARNING SYSTEM (CASE STUDY: BENGAWAN SOLO RIVER BASIN) - HADIANI, REVANA
As the largest river basin on the island of Java, areas of Bengawan Solo river basin are exposed to flooding each year. Precipitation is a major cause of natural hazards, particularily flooding. Due to the severity of a rainfall event and its potential damage is dependent on its intensity and duration, it is of utmost interest to estimate the rainfall thresholds and test their usefulness for the prediction of floods. Therefore, suitable rainfall threshold is necessary for flood early warning. The estimation of rainfall threshold is established based on precipitation measurements obtained from flood triggering rainfall events, through intensity-duration empirical threshold, using power law equation (Caine, 1980). Results show the flood triggering rainfall intensity-duration characteristic in Bengawan Solo river is predominantly low intensity rainfall events (1-5 mm/hr) which occur in moderate-long duration (? 6hr). The rainfall threshold for flood early warning in Bengawan Solo river basin is estimated by the following power law: I =1.476D0.512. After validated with flood events during wet season period of December-January-February 2016-2017, the threshold obtained shown to have decent accuracy with with hit rate 0.85.